Organization-Based Factors Bearing on Provider Screening and Referral Practices for Women Exposed to Intimate Partner Violence - Kosiak, Klaudia (Journal of interpersonal violence, 2022)
Essential steps in the provision of health care for women exposed to intimate partner violence (IPV) are screening and referral for specialized services, as might occur in primary care settings. Prior to participating in a cross-disciplinary IPV training program, medical care (N = 223) and social/behavioral practitioners (N = 197) completed a survey that ascertained current practices, provisions, and perceived barriers related to IPV screening and referral. Roughly half of the study participants did not routinely screen their patients/clients for IPV, with no differences for the professional groupings. Utilization of referral resources was significantly lower for medical care providers, 78.5% of whom did not use any. Perceived barriers to screening and referral were examined as practitioner-based and organization-based, and we identified tangible provisions (protocols and practice materials) as a relevant variable. As we conjectured, organization-based barriers were more strongly associated with lower rates of screening and referral than were practitioner-based barriers, regardless of professional grouping. Moreover, tangible provisions, controlling for perceived barriers, significantly added to routine screening and frequency of referral resources usage, particularly for medical care providers. Results are discussed in the context of a systems-level approach to improving IPV services in health care with organizational practice enhancements.